Acute Mountain Sickness: Symptoms, Diagnosis, Risk Factors, Prevention and Treatment - Śniatała, Alicja; Adamowska, Agnieszka; Grubski, Damian; Nadolny, Filip; Bartkowiak, Hanna; Jabłoński, Jędrzej; Ziarnik, Kacper; Kania, Martyna (Quality in Sport, 2024)
Introduction High mountain climbing has surged in popularity over the past few decades, attracting a diverse range of participants from professional athletes to even recreational enthusiasts, given that this sport has become commercial and more accessible. While high mountain climbing offers numerous mental and physical benefits, it also presents significant risks, among them one of the most dangerous is acute mountain sickness (AMS). Correct techniques of prevention are absolutely vital for the success of the expedition. To be able to read correctly the symptoms is essential for making the right decision during hike and knowing how to act once AMS occurs is necessary to ensure safety for all climbers. Aim of the study The purpose of this narrative is to comprehensively describe information about the prevention, symptoms and instructions concerning further procedure while dealing with acute mountain sickness (AMS). Materials and methods The methodology of the literature search involved using the keywords “acute mountain sickness” and adding terms such as “prevention”, “symptoms”, “diagnosis”, “risk factors” and “treatment”. The search terms were entered into the PubMed and Google Scholar databases. The review works and clinical trials were taken into account. Conclusion Acute mountain climbing occurs above 2500 m. The most important aspects of prevention and treatment is controlled ascent, rapid diagnosis and instant initiation of treatment, meaning descent. The pharmacologic prophylaxis and therapy is not recommended in every case, all of the decisions must be taken individually according to severity of symptoms and general situation in the mountains.